2021
DOI: 10.36565/jab.v10i1.290
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Self Efficacy terhadap Pemahaman Tanda Bahaya Kehamilan menggunakan Video dan Buku Kesehatan Ibu dan Anak

Abstract: One effort to increase the understanding of pregnant women about the danger signs of pregnancy is to carry out social persuasion in the form of education to improve self-efficacy of understanding the danger signs. Education can be done using a variety of media, namely visual media, audio and audio visual. This literature study aims to find out Effectiveness of Self-Efficacy towards Understanding of  Pregnancy Danger Signs using Videos and Books of MCH.The design used in this study is the study of literature. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 1 publication
0
2
0
14
Order By: Relevance
“…Previous quasi experimental research in 2017 also stated that video was more effective in increasing pregnant women's knowledge, attitudes and behavior compared to booklet media (Selvia et al, 2017). Subsequent research in 2021 also states that the use of videos increases the effectiveness of self-efficacy in understanding pregnancy danger signs compared to the KIA book (Herinawati et al, 2021). When compared with other studies, the opposite is shown by 2019 study which states that there is no significant different in the use of video media and leaflets (Nuradhawiyah, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Previous quasi experimental research in 2017 also stated that video was more effective in increasing pregnant women's knowledge, attitudes and behavior compared to booklet media (Selvia et al, 2017). Subsequent research in 2021 also states that the use of videos increases the effectiveness of self-efficacy in understanding pregnancy danger signs compared to the KIA book (Herinawati et al, 2021). When compared with other studies, the opposite is shown by 2019 study which states that there is no significant different in the use of video media and leaflets (Nuradhawiyah, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Dengan mengenal tanda bahaya kehamilan diharapkan ibu hamil dapat mendeteksi dan mencegah adanya bahaya atau ancaman dalam kehamilan, sehingga ibu hamil dapat segera mengambil keputusan dengan cepat untuk segera datang ketenaga kesehatan. Jika tanda bahaya kehamilan ini tidak terdeteksi dengan cepat maka dapat mengakibatkan AKI, AKB, kehamilan dengan komplikasi dan persalinan dengan patologi (Herinawati, 2021).…”
Section: Pendahuluanunclassified
“…Setiap ibu hamil pada kunjungan pertama kehamilan (K1) akan diberikan buku Kesehatan Ibu dan Anak (KIA). Informasi tentang tanda bahaya kehamilan tercantum dalam buku ini namun sebagian besar ibu hamil belum memanfaatkan Buku KIA [5].…”
Section: Pendahuluanunclassified
“…Pada kenyataan banyak ibu hamil yang kurang mengetahui tanda bahaya kehamilan [6]. Memahami tanda bahaya kehamilan dipengaruhi niat dan pengetahuan dari seorang individu [5].…”
Section: Pendahuluanunclassified
See 1 more Smart Citation